Strategi Pendidikan Nilai Islami di Perguruan Tinggi Umum - Herlina, Lenny (LP2M STIT Palapa Nusantara, 2019)
Regardless of the definition of education, as much as that is the formulation of the goals of education, including those determined on the basis of ideology. The purpose of education itself is